ショウワ キチ カンリ トウ ノ ケンセツ (1) キホン セッケイ - 半貫, 敏夫; ハンヌキ, トシオ; 小石川, 正男; コイシカワ, マサオ; 平山, 善吉; ヒラヤマ, ゼンキチ; 佐野, 雅史; サノ, マサシ; 佐藤, 稔雄; サトウ, トシオ; Hannuki, Toshio; Koishikawa, Masao; et al. (1993)
P(論文) 昭和基地建設の歴史的経緯をふまえて, 基地建物の現状と計画的な建物更新の必要性およびその概要を述べた。次いで昭和基地に建つ南極観測用建物の設計・製作に関する制約条件を整理し, これまでに昭和基地で試みられてきた極地建築システムについて概観した。国立極地研究所観測協力室の立案による昭和基地整備計画の最初の事業として企画された「管理棟」の基本構想をまとめるまでの経緯と基本設計の概要を紹介し, 建築・防災・構法などの新しい試みについて解説した。また, これからの南極観測用建築のありかたについても言及した。 The history of building construction at Syowa Station of Japanese Antarctic Research Expedition (JARE) was surveyed and the present condition of these buildings was discussed. It was pointed out that the living quarters consisting of the oldest buildings should be improved as early as possible. Design-conditions of the building at Syowa Station which were concerned with transportation, climate and construction in polar regions were arranged. The development and improvement of the building-prefabrication system at Syowa Station were reviewed. The design concept and the outline of preliminary design of the new central building which was planned as the first work of the reintegration project of Syowa Station were explained. Fire-preventive design and new wooden structural system with large-scale laminated timber were marked in the design. And future of the polar buildings was discussed. departmental bulletin paper